Reactive strength index as a key performance indicator in different athlete populations - A systematic review - Southey, B.; Willshire, M.; Connick, M. J.; Austin, D.; Spits, D.; Beckman, E. (Science & Sports, 2024)
Objectives Reactive Strength Index (RSI) is a neuromuscular assessment used to measure stretch-shortening cycle (SSC) function of the lower limb. Increased RSI scores have been frequently associated with running performance, such as faster sprint times, greater running economy and reduced change of direction times. These locomotor activities are involved in various sports and therefore, RSI is an important indicator of athletic capacity in sport. Whilst RSI has been commonly used in studies to assess SSC performance, no review has been conducted examining the difference in RSI between athletic populations. Thus, the aim of this systematic review was to summarise the literature and determine whether there was any significant difference in RSI between different populations and summarise the underlying factors contributing to these results.